Exploratory study of factors in group counselling that enhance a sense of connectedness in adolescent girls - Ho, Pamela Lei Kuan. (2008)
The primary objective of this study was to explore the therapeutic factors at work in group counselling. In particular, the current study investigated which of twelve therapeutic factors (Yalom, 1985) were perceived to be most important to the group members. These factors include altruism, group cohesiveness, universality, interpersonal input, interpersonal output, guidance, catharsis, identification, family re-enactment, self-understanding, instillation of hope and existential factors.